The Relationship between Competence and Job Satisfaction on the Performance of Private Madrasah Tsanawiyah Teachers in the City of Surabaya - Supriyanto, Supriyanto; Kusmaningtyas , Amiartuti; Nugroho, Riyadi (Journal of Asian Multicultural Research for Economy and Management Study, 2021)
This study aims to discuss the relationship between competence and job satisfaction on the performance of private Madrasah Tsanawiyah teachers in the city of Surabaya. The research method used is the type of research used that is explanatory with a quantitative approach with a sample size of 244 of 628 teachers from 44 private Madrasah Tsanawiyah in the city of Surabaya). The results showed that teachers’ competence had an effect on teachers’ job satisfaction with a value of 0.184. Teachers’ competence affected teachers’performance with a value of 0.118. Teachers’ job satisfaction affected teachers’ performance with a value of 0.222. Teachers’ job satisfaction on teachers’ performance showed a high influence with a CR value of 2.772 (greater than 2.00) and a significance level (p-value) of 0.006 (less than 5%). It can be concluded that teachers’ competence affected teachers’ job satisfaction and teachers’ competence affected teachers’ performance. Teachers’ job satisfaction had a strong effect on teachers’ performance.